Elevated Circulating Levels of Motilin are Associated with Diabetes in Individuals after Acute Pancreatitis - Gold-Smith, Fuchsia D.; Singh, Ruma G.; Petrov, Maxim S. (Experimental and Clinical Endocrinology & Diabetes, 2020)
Aim The study aimed to investigate the associations between glycaemic control after acute pancreatitis and gastrointestinal motility, using plasma motilin concentration and gastroparesis cardinal symptom index score as proxies.Methods This cross-sectional study recruited a total of 93 individuals after acute pancreatitis. Gastroparesis cardinal index scores, demographic and anthropometric factors, as well as pancreatitis-related factors were analysed. Fasting venous blood was collected to measure motilin, glycated haemoglobin, and fasting blood glucose. Linear regression analyses were conducted to investigate the associations between glycaemic control and gastrointestinal motility in unadjusted and adjusted models.Results Motilin was significantly higher in individuals with diabetes across all adjusted models, with the highest ß-coefficient (95% confidence interval) of 588.89 (138.50, 1039.28); P=0.010. Fasting blood glucose was significantly associated with motilin across all models, with the highest ß-coefficient (95% confidence interval) of 156.30 (55.49, 257.10); P=0.002. Glycated haemoglobin was significantly associated with motilin in one adjusted model with ß-coefficient (95% confidence interval) of 18.78 (1.53, 36.02); P=0.033. Gastroparesis cardinal symptom index was not significantly associated with any measure of glycaemic control.Conclusions Diabetes in individuals after acute pancreatitis appears to be characterised by elevated plasma motilin but not gastroparesis cardinal symptom index. The role of motilin in this setting warrants further investigations.
Keywords: acute pancreatitis; diabetes mellitus; gastroparesis; gastroparesis cardinal symptom index; motilin